ANALISIS INTERAKSI GURU FIQIH DALAM MENINGKATKAN MINAT BELAJAR PESERTA DIDIK KELAS VIII DI MTs RADHIATUL ADAWIYAH MANGGA TIGA MAKASSAR: Analysis Of Fiqih Teacher Interaction In Improving Learning Interest Of Grade Viii Students At Mts Radhiatul Adawiyah Mangga Tiga Makassar - Puja, Avrilia; Kamaruddin; Sudika, Aryandi; Indri Karadona, Rosika (STAI Ma'had Aly Al-Hikam Malang, 2025)
This study aims to evaluate how the interaction between fiqih teachers and students can enhance the learning enthusiasm of eighth-grade students at Madrasah Tsanawiyah Radhiatul Adawiyah Mangga Tiga Makassar. A qualitative approach with a descriptive study design was employed in this research. Data were collected through observation, interviews, and documentation. The findings indicate that the interaction between fiqih teachers and students during the learning process was generally positive, as evidenced by the communication that occurred between students and the application of various teaching methods. However, several challenges were identified, such as students’ lack of attention, low learning motivation, and limited availability of learning media. Some of the solutions implemented included improving teaching methods to be more engaging, applying more personal approaches to students, and fostering cooperation between teachers and parents to support the learning process. With effective teacher-student interaction, students' interest in learning increased, making fiqih lessons more meaningful.